2018
DOI: 10.4269/ajtmh.18-0309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Nonfatal Dengue Episode on Disability-Adjusted Life Years: A Systematic Analysis

Abstract: Abstract.As dengue causes about 4,000 symptomatic nonfatal episodes for every dengue death globally, quantitative disability assessments are critical to assess the burden of dengue and the cost-effectiveness of dengue control interventions. This systematic analysis of disability or quality of life lost from a symptomatic nonfatal dengue episode combined a systematic literature review, statistical modeling, and probabilistic sensitivity analyses. We conceptualized a dengue episode as having two phases: acute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…Another way to assess the impact of dengue on HRQoL is through the estimation of a disease burden metric such as DALYs. Using empirical data from 6 studies, Zeng et al, estimated that the first 20 days of a single episode of dengue are responsible for the loss of 0.012 years of healthy life [14]. Although the prediction of HRQoL scores was not the primary purpose of our multiple regression analysis using our model-predicted scores for males of the median age (16yrs) we calculated estimated DALYs for the first 20 days of a dengue episode for clinic, community and contact-cluster recruited participants.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another way to assess the impact of dengue on HRQoL is through the estimation of a disease burden metric such as DALYs. Using empirical data from 6 studies, Zeng et al, estimated that the first 20 days of a single episode of dengue are responsible for the loss of 0.012 years of healthy life [14]. Although the prediction of HRQoL scores was not the primary purpose of our multiple regression analysis using our model-predicted scores for males of the median age (16yrs) we calculated estimated DALYs for the first 20 days of a dengue episode for clinic, community and contact-cluster recruited participants.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The values can in turn be used to estimate disability adjusted life years (DALYs), a measure of the years of healthy life lost due to a certain illness in a given population [13]. A recent systematic analysis by Zeng et al used empirical data from 6 studies to estimate the disease burden of a single, nonfatal dengue episode [14]. The authors concluded that previous measures may have underestimated the disease burden of non-fatal dengue with the average episode of dengue being responsible for the loss of 0.032 years of healthy life [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other symptoms also reported include vomiting, diarrhoea, nausea, chills, and poor appetite [4]. Both hospitalized patients and outpatients can experience these post-acute consequences and they have not been shown to associate with the severity of the acute episode [4,8]. Furthermore, postacute consequences were usually associated with female gender and older age [3,4,9].…”
Section: The Post-acute Consequences Of Dengue Infectionmentioning
confidence: 99%
“…Abbreviations: YLDs: years of healthy life lost due to disability, YLLs: years of life lost due to premature death. of patients experiencing any fatigue or trouble working after recovery from dengue [6,8]. It was noteworthy that the time that the majority of studies followed up patients was short.…”
Section: The Post-acute Consequences Of Dengue Infectionmentioning
confidence: 99%